Workload of Medical Record Service in Pandemic Covid-19 - Sri Wahyuningsih Nugraheni; Erna Zakiyah; Mamik Farida (LPPM Universitas Duta Bangsa Surakarta, 2021)
The workload of hospital staff, especially registration officers at RSUI YAKSSI Gemolong Sragen, in 2020 has decreased and increased along with the decline and increase in the number of patients during the COVID-19 pandemic. The calculation of the need for the number of registration officers uses the health workload analysis method (ABK Health). The aim of this study was to analyze the workload of registration officers and calculate the need for the number of registration officers using the health workload analysis method (ABK Health). This research is a descriptive study with cross sectional approach. Research subjects were manajer of the medical record, manajer of the registration room, and the registration officer. While the object of research is the registration officer workload in RSUI YAKSSI Gemolong Sragen. The research instruments were observation and interview guidelines. Data processing by collecting, editing, tabulating and presenting data. Analysis data is descriptively. The steps of the ABK Health method include determining health service facilities and types of human resources, determining available work time, determining workload components and work norms, calculating workload standards, calculating standards of supporting activities, then calculating the human resource needs for health per health service institutions or facilities. Based on the calculation of the need for registration officers at RSUI YAKSSI in 2020 a number of 6, and currently there are 6 registration officers at RSUI YAKSSI so that is sufficient. The need for registration officers at RSUI YAKSSI in 2020 is 6, and currently there are 6 registration officers at YAKSSI Hospital so that is sufficient. The number of registration officers is sufficient, however, it is necessary to improve the quality of registration officers with further education for registration officers with high school education qualifications to diploma 3 educational qualifications of medical records and health information.